Study of coaggregation/autoaggregation ability of bacterial isolates isolated from Tertiary Butyl Alcohol (TBA) degrading consortia - Kerk, Wei Yi. (2009)
Five types of bacterial strains isolated from Tertiary Butyl Alcohol (TBA) degrading consortia were tested for their autoaggregation and coaggregation abilities. Bacterial aggregation is important in wastewater treatment processes such as activated sludge and biogranulation systems. The five types of bacterial strains tested are strain AL-001, strain AL-003B, strain AL-004, strain ACL-F-001A and strain TBA. Strain AL-003B shows the highest autoaggregation ability with an aggregation index of 33.11 % while the coaggregation assay of strain AL-004 with strain AL-003B shows the highest coaggregation ability with an aggregation index of 31.45 % at the end of five hours of aggregation experiments. This investigation also shows the importance of the type of gram stains on the coaggregation abilities of the five different types of bacterial strains.